Engine emission control technologies : design modifications and pollution mitigation techniques - Rao, G. Amba Prasad, 1966-; Sharma, T. Karthikeya, 1985- (Burlington, ON ; Palm Bay, Florida : Apple Academic Press Inc., 2020)
"This new volume, Engine Emission Control Technologies, covers many important issues related to environmental emissions from SI and CI engines, their formation, and various pollution mitigation techniques. The book addresses aspects of improvements in engine modification, such as design modifications for enhanced performance, both with conventional fuels as well as with new and alternative fuels. It also explores some new combustion concepts that will help to pave the way for complying with new emission concepts. Alternative fuels are addressed in this volume to help mitigate harmful emissions, and alternative power sources for automobiles are also covered briefly to entirely switch over from fueled engines to electrics, including battery-powered electric vehicles and fuel cells. The authors explain the different technologies available to date to overcome the limitations of conventional prime movers (fueled by both fossil fuels and alternative fuels). Topics examined include : engine modifications needed to limit harmful emissions, the use of engine after-treatment devices to contain emissions, the development of new combustion concepts, adoption of alternative fuels in existing engines, switching over to electrics-advantages and limitations, specifications of highly marketed automobiles, and emission measurement methods. Written in clear language and with over 100 illustrations, this volume will be highly useful for both students, research scholars, faculty, engineers, and other industry professionals"--
Basic Review of Internal Combustion Engines -- Formation Mechanism of Pollutant Emissions -- Emissions Measurement Methods and Instrumentation -- SI-in-Cylinder Measures -- SI-Aftertreatment Measures -- Diesel-in-Cylinder Measures -- Diesel-Aftertreatment Measures -- Alternative Fuels -- Alternative Combustion Concepts.
OCLC-licensed vendor bibliographic record.
Keywords: Automobiles -- Pollution control devices -- Design and construction; Automobiles -- Motors -- Design and construction; SCIENCE / General; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Environmental Engineering & Technology